PENGELOLAAN PEMBINAAN KEAGAMAAN ISLAM PADA NARAPIDANA DI RUMAH TAHANAN NEGARA KELAS II B PINRANG - Heriadi Heriadi (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
The purpose of this study was to determine the shape and effectiveness of management coaching Religious on Inmates at the State Prison Class IIB Pinrang. His research is descriptive - qualitative do research intensive, detail and depth to an institution or organization. Data were collected through interviews, documentation and observation. The results of the interview, documentation and observation are then analyzed with descriptive techniques. Examination of the validity of the data carried by the data reduction means summarizing, choose things that are the subject then presenting the data and draw conclusions from the research results. Based on analysis of data obtained from the research findings at the State Prison Class IIB Pinrang namely (1) the form of implementation guidance Islamic religious to prisoners in the State Prison Class IIB Pinrang is: Duha prayer, prayers, religious lectures, and learning to read Aquran. In addition to coaching is done on a regular basis, there is also carried out routine not only on a particular event, namely: Ramadan in Rutan and Day of the Islam. (2) the effectiveness of the religious development of Islam in State Prison Class IIB Pinrang can be quite successful, although not performing optimally. It can be found with many improvements occurred against religious knowledge inmates as evidenced by their ability to read the Koran but requires hard work and a long process, the depth of the spiritual increases with the presence of several inmates who changed the character and find peace after being in prison. Was concluded that, the management of Islamic religious guidance to prisoners of great benefit and the benefit that can be felt by all parties, either by inmates, the families of prisoners, the public or by Rutan itself. But the result of the construction that has been achieved still needs to be improved.